Gold nanobipyramids-based laser-activated sealants for effective skin sealing and repair - Shubham Pallod; Gareth Fuller; Trishita Chowdhury; Kaushal Rege (International Journal of Hyperthermia)
Anisotropic gold nanostructures have gained increased attention for biomedical applications because of their remarkable optical properties. An emerging type of gold nanostructure—gold nanobipyramids (AuNBP)—has been shown to exhibit superior absorption properties compared to conventionally used gold nanoparticles, which makes them attractive for photothermal applications. We generated a high-shape-purity dispersion of AuNBP using a seed-mediated method and embedded them as photothermal conversion agents in a silk fibroin matrix to investigate their efficacy in photothermal sealing of incisional wounds in immunocompetent mice. These AuNBP-doped laser-activated sealants, or AuNBP-LASE were able to absorb near-infrared laser energy and convert it to heat, thereby inducing transient hyperthermia in the wound and the surrounding tissue. This photothermal conversion facilitated rapid sealing of the skin tissue by the AuNBP-LASE, which resulted in faster functional recovery of skin barrier function compared to nylon sutures at the early stages of repair. Further, the biomechanical properties of the healing skin closed with AuNBP-LASE those of intact skin more rapidly compared to incisions approximated with sutures. Histology studies indicated higher penetration of the LASE within the volume of the incision in skin tissue, lower scab formation, and a similar epidermal gap compared to conventional suturing. These results demonstrate that AuNBP-LASEs can be effective as wound approximation devices for photothermal sealing.